Dopamine D1/D5, But not D2/D3, Receptor Dependency of Synaptic Plasticity at Hippocampal Mossy Fiber Synapses that Is Enabled by Patterned Afferent Stimulation, or Spatial Learning - Hagena, Hardy; Manahan-Vaughan, Denise (Frontiers in Synaptic Neuroscience, 2016)
Although the mossy fiber (MF) synapses of the hippocampal CA3 region display quite distinct properties in terms of the molecular mechanisms that underlie synaptic plasticity, they nonetheless exhibit persistent (>24h) synaptic plasticity that is akin to that observed at the Schaffer collateral (SCH)-CA1 and perforant path (PP)-dentate gyrus (DG) synapses of freely behaving rats. In addition, they also respond to novel spatial learning with very enduring forms of long-term potentiation (LTP) and long-term depression (LTD). These latter forms of synaptic plasticity are directly related to the learning behavior: novel exploration of generalized changes in space facilitates the expression of LTP at MF-CA3 synapses, whereas exploration of novel configurations of large environmental features facilitates the expression of LTD. In the absence of spatial novelty, synaptic plasticity is not expressed. Motivation is a potent determinant of whether learning about spatial experience effectively occurs and the neuromodulator dopamine plays a key role in motivation-based learning. Prior research on the regulation by dopamine receptors of long-term synaptic plasticity in CA1 and dentate gyrus synapses in vivo suggests that whereas D2/D3 receptors may modulate a general predisposition toward expressing plasticity, D1/D5 receptors may directly regulate the direction of change in synaptic strength that occurs during learning. Although the CA3 region is believed to play a pivotal role in many forms of learning, the role of these receptors in persistent (>24h) forms of synaptic plasticity at MF-CA3 synapses is unknown. Here, we report that whereas pharmacological antagonism of D2/D3 receptors had no impact on LTP or LTD, antagonism of D1/D5 receptors significantly impaired LTP and LTD that were induced by solely by means of patterned afferent stimulation, or LTP/LTD that are typically enhanced by the conjunction of afferent stimulation and novel spatial learning. These data indicate an important role for dopamine acting on D1/D5 receptors in the support of long-lasting and learning-related forms of synaptic plasticity at MF-CA3 synapses and provide further evidence for an important neuromodulatory role for this receptor in experience-dependent synaptic encoding in the hippocampal subfields.